(untitled) (Medico Legal Update, 2020)
Human trafficking is a crime carried out by a dark society of some people, and its network is between countries and in international borders. Most victims come from developing countries. The main aim of this crime is to force young boys and girls to work in sexual sectors. There is economic oppression as they are exploited for the interests of the agents, distributors, and crime syndicates as what is similar to other illegal activities which regard trafficking, such as trafficking of domestic workers, fake marriage, illegal jobs, and illegal adoption. This research analyzes the legal protection for human trafficking victims and the health impacts. This is a doctrinal legal research, strengthened by the qualitative field research. It uses the constitutional and case approaches. Based on the results of the study and the discussion, it can be concluded that there are some impacts of the child trafficking in the aspects health and other aspects for the children. T The government needs to formulate and to refine the constitutional regulations regarding the health protection for victims of child trafficking